2022
DOI: 10.3390/jimaging8050139
|View full text |Cite
|
Sign up to set email alerts
|

Intraretinal Layer Segmentation Using Cascaded Compressed U-Nets

Abstract: Reliable biomarkers quantifying neurodegeneration and neuroinflammation in central nervous system disorders such as Multiple Sclerosis, Alzheimer’s dementia or Parkinson’s disease are an unmet clinical need. Intraretinal layer thicknesses on macular optical coherence tomography (OCT) images are promising noninvasive biomarkers querying neuroretinal structures with near cellular resolution. However, changes are typically subtle, while tissue gradients can be weak, making intraretinal segmentation a challenging … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Documented OCT measurements include the average pRNFL thickness, GCL or GCC as collected by the different platforms (e.g., Spectralis measuring GCL, Zeiss measuring GCC). The OCT images will subsequently be analyzed using post-hoc analysis with semi-automatic, device-independent algorithms (70).…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Documented OCT measurements include the average pRNFL thickness, GCL or GCC as collected by the different platforms (e.g., Spectralis measuring GCL, Zeiss measuring GCC). The OCT images will subsequently be analyzed using post-hoc analysis with semi-automatic, device-independent algorithms (70).…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The method was evaluated on a dataset containing MS patients and controls, reporting a drop in performance on the MS patients when compared with controls. In [47], the authors proposed the use of a cascaded two-stage network, with each stage being composed of a compressed version of U-Net. A post-processing stage was incorporated in which a Laplacian-based outlier detection is applied, followed by an adaptive non-linear interpolation with the intention of filling any inconsistent holes in the segmentation.…”
Section: B Related Workmentioning
confidence: 99%
“…The contour surrounding every layer was extracted both from each ground truth and automatically segmented output image. Following other related retinal layer segmentation works (for reference, [41], [42], [47]), the Mean Absolute Error (MAE) was computed between the pixel heights for every image column as a measurement of contour error (MAE C ), along with the MAE for the thickness of each layer (MAE T ). In order to provide a robust measurement of these metrics, and following other similar approaches in the literature [65], [66], bootstrapping with 1000 repetitions was applied at the image level to all tests.…”
Section: E Evaluationmentioning
confidence: 99%
“…He et al [ 26 ] trained a residual U-Net with two output branches for two probability maps of the retinal layers and junction surfaces and merged probability maps in an iterative surface topology module to estimate the retinal surface locations. Furthermore, Yadav et al [ 27 ] proposed a cascaded two-stage design, in which the first U-Net identified the retina in 2D OCT B-scan and the following U-Net focused on identifying each retinal layer based on the pre-segmented retina. Most recently, He et al [ 28 ] aimed to segment longitudinal OCT scans by proposing a long-short-term-memory U-Net (LSTM-UNet) to incorporate adjacent 2D B-scans information and convert the segmented surfaces as longitudinal priors.…”
Section: Introductionmentioning
confidence: 99%